The Role of Political PR and General Information Communication in the Development of Community (International Journal of Psychosocial Rehabilitation, 2020)
This article analyzes the role of political management and political PR in the process of modernization of the political system in today's globalization, which has not been sufficiently studied in the field of political science, the mental and universal characteristics, the horizontal and corporate governance in the conditions of democracy—the criteria and demand of political PR development. Besides, it also shows the importance of political PR technologies in election campaigns and controlling communicative processes and individual relations. One of the main functions of PR technologies and mass media communication is to further develop the political culture of the society, and the current role of the mass media in the socio-political life of the society has been revealed with the relevant examples.